Extinction limit and near-limit kinetics of lean premixed stretched H2-CO-air flames. (19th October 2016) - Zhang, Yang; Shang, Rongxue; Shen, Wenfeng; Zhu, Mingming; Zhang, Zhezi; Zhang, Hai; Zhang, Dongke
Abstract: The extinction limit of laminar lean premixed stretched H2 -CO-air flames was investigated with particular attention to the chemical kinetic characteristics under near-limit conditions. The extinction stretch rates were determined by the digital particle image velocimetry measurement using the Counterflow Twin-Flame method. Corresponding numerical simulations were conducted using CHEMKIN II with detailed chemical kinetic mechanisms. The simulation results generally agreed well with the experimental data. It was found that increasing H2 ratio restrained the flame from being extinguished, and this restraining effect was more profound low H2 ratios. Further analyses of the flame speed, temperature and elementary reaction sensitivities revealed that H2 addition played a crucial role in flame extinction by changing the competition between chain branching and termination reactions. To quantitatively measure the kinetic effect of H2 addition, a dimensionless extinction exponent ( β ) defined as the ratio between the relative sensitivities of termination ( ω T ) and branching ( ω B ) reaction rates, i.e., β = ∂ln ω T /∂ln ω B, was proposed. For a given syngas, β rapidly increased to a certain constant, defined as the critical extinction exponent, when the flame extinction was approached, despite variations in the stretch rate and changes in the loss mechanism. The chemical kinetic characteristics and loss mechanism jointly determined the extinction limit of lean premixed H2 -CO-air flames. Highlights: Extinction limits of lean premixed H2 -CO-air flames were measured and computed. H2 addition restrains the flames from being extinguished. Chemical kinetics is crucial in determining the H2 -CO-air flame extinction. An extinction exponent was proposed based on the chain theory. The critical extinction exponent characterises the near-limit kinetics.